An Assessment of Ghana's Corruption Struggle; the Role of Political Parties - Stephen Delle Donpaala; Musah Alhassan; Emmanuel Yelku-ang Dabuo (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Political parties play a significant role in the functioning of robust democracies, and consequently, they are held to high expectations, particularly with regards to addressing issues of corruption. In nearly all countries globally, political parties are inherently linked to the issue of corruption due to their role in selecting and electing leaders who govern nations and possess constitutional control over national resources. Therefore, they play a crucial role in either combating corruption or facilitating corruption. In the realm of assessment, Ghana, as a sovereign state since its attainment of independence, has encountered persistent challenges with corruption, which, according to existing evidence, seems to be escalating over time. Nearly every governmental entity is grappling with the pervasive issue of corruption. Furthermore, political parties are frequently perceived as entities that exploit their influential status to solicit bribes, allocate lucrative posts in the public sector to its members and followers, or divert public resources towards the control of party leaders or supporters. Corruption poses significant challenges in developing and transitional nations such as Ghana, where political institutions grapple with many manifestations of corrupt practises. Corruption erodes public trust in governing institutions and poses a significant challenge to the sustainability of democratic systems. In a competitive political context, democratic parties have the capacity to fulfil significant political roles and duties, particularly in combating corruption through many means. Although political parties are frequently associated with corruption, scholarly discussions on corruption and anti-corruption measures have acknowledged that if political parties assume the crucial role of combating corruption, it could result in significant progress. Therefore, this study evaluates the ongoing battle against corruption in Ghana, with a specific focus on the involvement of political parties. Furthermore, the study utilised secondary data for analysis, which informed the subsequent conclusions and recommendations.